Potential Adverse Effects of Prolonged Sevoflurane Exposure on Developing Monkey Brain: From Abnormal Lipid Metabolism to Neuronal Damage - Liu, Fang (Toxicol Sci, 2015)
Sevoflurane is a volatile anesthetic that has been widely used in general anesthesia, yet its safety in pediatric use is a public concern. This study sought to evaluate whether prolonged exposure of infant monkeys to a clinically relevant concentration of sevoflurane is associated with any adverse effects on the developing brain. Infant monkeys were exposed to 2.5% sevoflurane for 9 h, and frontal cortical tissues were harvested for DNA microarray, lipidomics, Luminex protein, and histological assays. DNA microarray analysis showed that sevoflurane exposure resulted in a broad identification of differentially expressed genes (DEGs) in the monkey brain. In general, these genes were associated with nervous system development, function, and neural cell viability. Notably, a number of DEGs were closely related to lipid metabolism. Lipidomic analysis demonstrated that critical lipid components, (eg, phosphatidylethanolamine, phosphatidylserine, and phosphatidylglycerol) were significantly downregulated by prolonged exposure of sevoflurane. Luminex protein analysis indicated abnormal levels of cytokines in sevoflurane-exposed brains. Consistently, Fluoro-Jade C staining revealed more degenerating neurons after sevoflurane exposure. These data demonstrate that a clinically relevant concentration of sevoflurane (2.5%) is capable of inducing and maintaining an effective surgical plane of anesthesia in the developing nonhuman primate and that a prolonged exposure of 9 h resulted in profound changes in gene expression, cytokine levels, lipid metabolism, and subsequently, neuronal damage. Generally, sevoflurane-induced neuronal damage was also associated with changes in lipid content, composition, or both; and specific lipid changes could provide insights into the molecular mechanism(s) underlying anesthetic-induced neurotoxicity and may be sensitive biomarkers for the early detection of anesthetic-induced neuronal damage.